Progesterone Attenuates Allodynia of Inflamed Temporomandibular Joint through Modulating Voltage-Gated Sodium Channel 1.7 in Trigeminal Ganglion. (26th July 2020) - Bi, Rui-Yun; Zhang, Xiao-Yu; Zhang, Peng; Ding, Yun; Gan, Ye-Hua
Abstract : Background . Women with temporomandibular disorders (TMDs) experience some amelioration of pain during pregnancy. Progesterone increases dramatically and steadily during pregnancy. Sodium channel 1.7 (Nav1.7) plays a prominent role in pain perceptions, as evidenced by deletion of Nav1.7 alone leading to a complete loss of pain. In a previous study, we showed that Nav1.7 in trigeminal ganglion (TG) is involved in allodynia of inflamed temporomandibular joint (TMJ). Whether progesterone modulates allodynia of inflamed TMJ through Nav1.7 in TG remains to be investigated. Methods . The effects of progesterone on sodium currents of freshly isolated TG neurons were examined using whole-cell recording. Female rats were ovariectomized and treated with increasing doses of progesterone for 10 days. Complete Freund's adjuvant was administered intra-articularly to induce TMJ inflammation. TMJ nociceptive responses were evaluated by head withdrawal thresholds. Real-time PCR and Western blotting were used to examine Nav1.7 mRNA and protein expression in TG. Immunohistofluorescence was used to examine the colocalization of progesterone receptors (PR α / β ) and Nav1.7 in TG. Results . Whole-cell recording showed that progesterone could attenuate sodium currents. Moreover, progesterone dose-dependently downregulated Nav1.7 mRNA expression and reduced the sensitivity of TMJ nociception in ovariectomized rats. Furthermore, treatment with progesterone attenuated allodynia of inflamed TMJ in a dose-dependent manner and repressed inflammation-induced Nav1.7 mRNA and protein expression in ovariectomized rats. The progesterone receptor antagonist, RU-486, partially reversed the effect of progesterone on allodynia of inflamed TMJ and TMJ inflammation-induced Nav1.7 mRNA and protein expression. Conclusion . Progesterone, by modulating trigeminal ganglionic Nav1.7, may represent a promising agent to prevent allodynia of inflamed TMJ.